Feasibility of using photovoltaic solar energy for water treatment plants - Alexander Saavedra; Nataly Alejandra Galvis; Mónica Castaneda; Sebastian Zapata; Fredy Mesa; Andrés Julián Aristizábal (Institute of Advanced Engineering and Science, 2021)
The purpose of this research is to determine the feasibility of supplying photovoltaic solar energy for the electrical requirements of drinking water and wastewater treatment plants, in six regions of Colombia, with different geographic and climatological conditions: Andean Region, Amazon Region, Orinoquía Region, Caribbean Region, Pacific Region, and Insular Region. The study revealed that the costs of the photovoltaic systems oscillate between USD 32,486.86 and USD 40,716.86, without using a storage system with batteries, since the price of these makes the investment recovery unfeasible. Instead of using batteries to store energy, a water storage system is used. The total daily load of the sanitation systems is 57 kWh/day, which would avoid 7120.44 kgCO2 per year. Besides, during the entire useful life of the 20-year project, 142.4 tCO2 would not be released into the environment.